Extraction and characterization of acid-soluble collagen and pepsin-soluble collagen from the dry scales of the striped snakehead (Channa striatus) - Bagus Fajar Pamungkas; Supriyadi Supriyadi; Agnes Murdiati; Retno Indrati (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2018)
Characteristics of collagen are influenced by the source of raw materials and extraction methods used. The aim of this research was to characterize the acid- and pepsin-soluble collagens from the dry scales of the striped snakehead (Channa striatus). Collagen was extracted using to methods including 0.5 M acetic acid and 0.1% pepsin. The yield of acid soluble collagen (KLA-SH) and pepsin soluble collagen (KLP-SH) were 0.98% and 1.94%, respectively. KLA-SH and KLP-SH contained glycine as the major amino acid and had high imino acid group content i.e 226 and 230 residues/1.000 residues, respectively. FTIR spectra of KLA-SH and KLP-SH showed that of the structure of collagen could be maintained in the form of triple helix structure. KLA-SH and KLP-SH consisted of α1- and α2-chain, β-chain, and γ-chain and is suggested as type I collagen.